Intellectual disability : understanding its development, causes, classification, evaluation, and treatment - Harris, James C. (Developmental perspectives in psychiatry., 2006)
Provides professionals with information on mental retardation disabilities. This work reviews various types of intellectual disabilities, discusses approaches to classification, diagnosis, and appropriate interventions, and provides information on resources that may offer additional help.